2005
DOI: 10.1177/0739986305278130
|View full text |Cite
|
Sign up to set email alerts
|

Medical Pluralism in the Life of a Mexican Immigrant Woman

Abstract: This case study reflects on the variety of approaches to health care in a pluralistic immigrant urban enclave in Southern California. In-depth interviews were conducted with a Mexican immigrant woman to explore and understand her health worldview and the strategies she uses in deciding among the diverse health care options available to protect and maintain her family's health. Kleinman's typology of health sectors (professional, folk, and popular) is applied to the popular healing practices of the key inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…However, it is doubtable that this essentialist perspective is applicable beyond a theoretical framework, since several studies have shown that migrants neither completely abandon traditional medical practices and health beliefs, nor totally reject the majority culture's health care system (Capps, 1994;Zapata and Shippee-Rice, 1999;Pieroni and Vandebroek, 2007;Pieroni et al, 2007a). Yet, it seems logical that many migrants, especially the most vulnerable ones -in both socio-economic and legal terms -tend to make more use of their own medical help-seeking strategies (Belliard and Ramírez-Johnson, 2005). Many illegal migrants have restricted access to services, which can have serious implications for their physical and mental health.…”
Section: Introductionmentioning
confidence: 98%
“…However, it is doubtable that this essentialist perspective is applicable beyond a theoretical framework, since several studies have shown that migrants neither completely abandon traditional medical practices and health beliefs, nor totally reject the majority culture's health care system (Capps, 1994;Zapata and Shippee-Rice, 1999;Pieroni and Vandebroek, 2007;Pieroni et al, 2007a). Yet, it seems logical that many migrants, especially the most vulnerable ones -in both socio-economic and legal terms -tend to make more use of their own medical help-seeking strategies (Belliard and Ramírez-Johnson, 2005). Many illegal migrants have restricted access to services, which can have serious implications for their physical and mental health.…”
Section: Introductionmentioning
confidence: 98%
“…Medical pluralism denotes that multiple models of health and illness exist in a society, that the models have distinct health beliefs and treatment strategies, and that individuals choose among these models for health care based on diverse factors, including availability, cost, and health condition [2223]. Pluralistic health systems that include biomedical and traditional health beliefs and treatment have been studied in numerous contexts [2426]. Hierarchy of resort refers to the order in which individuals select the use of difference health care models and practices [2731].…”
mentioning
confidence: 99%
“…One aspect of indigenous culture that has undergone considerable change is the system of traditional medicine, i.e. the health knowledge, beliefs, values, skills and practices of indigenous people, including all clinical and non-clinical activities and institutions that relate to the health needs of the people (Belliard & Ramírez-Johnson, 2005;Colvard et al, 2006). In spite of a significant amount of research that has been conducted on traditional medical practices in several Latin American countries, changes occurring within urban areas have not been a focus of research (Barnes et al, 2007).…”
Section: Processes Of Change and Adaptation In Traditional Medicinementioning
confidence: 99%